Modification of the mesoscopic structure in neutron irradiated EPDM viewed through positron annihilation spectroscopy and dynamic mechanical analysis - Lambri, Osvaldo Agustin F. (2011)
This article focuses on the study of the mesoscopic structure in neutron irradiated EPDM both from experimental and theoretical points of view. In this work we reveal completely the modification of the mesostructure of the EPDM due to neutron irradiation, resolving volume fraction, size and distribution of the crystalline zones as a function of the irradiation dose. Positron annihilation spectroscopy and dynamic mechanical analysis techniques are applied and the results are discussed by means of new theoretical results for describing the interaction process between the crystals and amorphous zones in EPDM.